Buddhism, Wealth, and Privilege: Ambedkar and Habermas - San, Pisith (Religions, 2023)
This essay compares key essays on Buddhism by B.R. Ambedkar and Jürgen Habermas vis-à-vis the issue of Buddhism, wealth, and privilege, and the respective statements again to what the Buddha taught, from a Theravada perspective. In doing so, it can be seen that Buddhism does not indeed endorse privilege in this world—but what seems to be privilege and inherited wealth are actual merits from a former life. Since these come with their own dangers, viz. attachment and not putting wealth to good use, wealth may be nice but not more. That someone is better than someone else because of birth and inheritance rather than action is, however, established as completely non-Buddhist, again and again, even by the Buddha himself.